Plastic limit load of Grade 91 steel pipe containing local wall thinning defect at high temperature. (November 2015) - Xue, Jilin; Zhou, Changyu; Lu, Xiaofeng; Yu, Xiaochun
Abstract: This paper aims to predict the plastic limit load of Grade 91 pipe at high temperature by experimental and numerical analysis methods. The elastic–plastic constitutive relation of P91 considering creep damage at high temperature is proposed and the effectiveness is verified by high-temperature instantaneous tensile test after creep of P91 sample. Then, using the elastic–plastic constitutive relation considering creep damage, the plastic limit loads of P91 pipe containing local wall thinning (LWT) defect at high temperature have been calculated by finite element (FE) method and the accuracy is checked by high-temperature burst experiment after creep of T91 pipe containing LWT. Finally, the fracture analysis and metallographic analysis of Grade 91 sample and pipe containing LWT defect are performed. The results show that the elastic–plastic constitutive relation of P91 considering creep damage proposed by this paper can well describe the elastic–plastic behavior of P91 under creep condition and is useful to calculate the plastic limit load of P91 pipe containing LWT. The failures of P91 tensile samples and T91 pipes containing LWT defect are both plastic fracture. This research would provide an optional method for structure integrity analysis of the pipe containing LWT defect at high temperature. Highlights: Elastic–plastic constitutive relation of P91 considering creep damage is proposed. Effectiveness of elastic–plastic constitutive relation is verified by tensile test. Plastic limit loads of pipe with LWT at high temperature are calculated by FE method. Plastic limit loads calculated by FE method are verified by pipe burst experiment. Failure analysis of Grade 91 sample and pipe containing LWT defect is performed.